EC merger control - Cook, C. J. [ (C. John)]; Kerse, Christopher (Sweet & Maxwell, 2009)
Now in its 5th edition, this well-respected work provides a comprehensive analysis of the EC merger control regime. The book examines the impact of legislative and procedural changes made in 2004 on